(untitled) (Acta Scientiarum. Education, 2021)
Mobile learning (mlearning) has been emerging as an innovation with incredible potential to transform the educational practice. However, limited research has focused on how mlearning has been investigated in the context of language teaching and learning around the world. This paper presents a survey on the educational scenario that pervades the teaching and learning English as a second or foreign language mediated by technology. This study conducted an analysis of publications (N=18) involving mlearning in the context of teaching or learning English as a foreign or second language and published from 2010 to March 2019. The aims were to verify in what perspective mlearning has been investigated in the context of teaching and/or learning a foreign or second language, what critical success factors (CSFs) have influenced the implementation of mlearning and identify possible gaps of study that need to be fulfilled in future researches. The results indicate that: i) mlearning has been most investigated in the tertiary educational level, ii) the learners` perspective has been the focus of most publications, iii) English is the target language in all studies, and iv) the dominant topic concerning this theme is mlearning technologies, apps and uses. In addition, the findings also report that 19 CSFs were pointed out in 14 publications and assimilation of curriculum (50%) was the most cited CSF. Moreover, the results indicate that there has been a recent increase of interest in mlearning related to foreign language teaching and learning. Further topics of investigation concerning mlearning in language education are suggested.